Estudios sobre la Hamartigenia de Prudencio II: lectura y análisis de su Prefacio - Encuentra Ortega, Alfredo, 1968- (2016)
Typology and allegory pervade the preface of Prudentius’ Hamartigenia, which traces the origin of sin back to Cain’s sacrifice, wrong division, and fratricide. Typology links both Adam to Christ and Cain to Marcion, and allegory presents fratricide as an assault of the flesh upon the mind, her sister. But Marcion and his sacrifice are also types of Mani and the main rite of the Manichaean church, the sacred meal of the Electi. On the basis of contending churches, Prudentius deploys Manichaean concepts and images, only recognisable to initiates, and gives them a new meaning compatible to the Nicene faith. Manichaean readership is thus exhorted to conversion. This preface anticipates the themes and communicative approach of the subsequent Hamartigenia, and shows the influence of Ambrose’s De Cain et Abel and some of Augustine’s anti-Manichaean works.
Keywords: Prudencio Clemente, Aurelio; Crítica textual